2017
DOI: 10.1093/nar/gkx140
|View full text |Cite
|
Sign up to set email alerts
|

The impact of base stacking on the conformations and electrostatics of single-stranded DNA

Abstract: Single-stranded DNA (ssDNA) is notable for its interactions with ssDNA binding proteins (SSBs) during fundamentally important biological processes including DNA repair and replication. Previous work has begun to characterize the conformational and electrostatic properties of ssDNA in association with SSBs. However, the conformational distributions of free ssDNA have been difficult to determine. To capture the vast array of ssDNA conformations in solution, we pair small angle X-ray scattering with novel ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 58 publications
18
71
0
Order By: Relevance
“…Strand T had fewer excess ions than the other five strands, which had similar values. This is consistent with results reported for dT 30 and dA 30 that were obtained from ICP‐AES, which showed that there were more excess ions associated with dA 30 [26]. In our work, strand T has the fewest excess ions and should therefore have the largest effective charge and, ignoring differences in effective mass due to intrinsic differences in base composition as well as differences in numbers of excess ions traveling with the strand, the highest µ EP .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Strand T had fewer excess ions than the other five strands, which had similar values. This is consistent with results reported for dT 30 and dA 30 that were obtained from ICP‐AES, which showed that there were more excess ions associated with dA 30 [26]. In our work, strand T has the fewest excess ions and should therefore have the largest effective charge and, ignoring differences in effective mass due to intrinsic differences in base composition as well as differences in numbers of excess ions traveling with the strand, the highest µ EP .…”
Section: Resultssupporting
confidence: 92%
“…In Tris buffer, where sequence‐based separation was not obtained in CZE [11], there were no significant differences among the R g values of the 15mers. In 0.14 M K‐PO 4 buffer, where separation was achieved, R g did show differences: R g was significantly smaller for T than for the other strands, followed by A and G, and then by the strands containing both A and G. This result is consistent with a previous report in the literature [26], in which SAXS data were analyzed using ensemble fitting methods to compare the global properties of single‐stranded 30mers (dT 30 and dA 30 ) at high salt concentrations. They found that the mean R g from transient conformation distributions was almost identical, but the transient conformation distributions showed different populations for certain conformations [26].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations